DKP Equation with Energy Dependent Potentials. (September 2019) - Langueur, O.; Merad, M.; Hamil, B.
Abstract: In this work, we study the DKP equation subjected to the action of combined vector plus scalar energy depend on potentials in (1+1) dimensions space-time. The conditions of normalisation and continuity equation are calculated. The eigenfunctions and the corresponding eigenvalues are then determined. A numerical study is presented and the energy graphs for some values of the energy parameter are plotted.